A two-way interactive teaching-learning process to implement flood disaster education in an early age: the role of learning materials - Azmi, Ezza Sabrina; Abdul Rahman, Haliza; How, Vivien (Universiti Putra Malaysia, 2020)
Introduction: Mainstreaming disaster education at the school level has been seen as an initiative in disaster risk mitigation to promote sustainable public awareness, however, the challenges to ensure an effective knowledge transfer has widely been highlighted. Educators who are lacking disaster education background always find it difficult in knowledge delivery and trigger learners' curiosity in disaster learning. Therefore, this study aims to evaluate the effectiveness of knowledge transfer in disaster learning among school children by using two different learning methods with the same learning module. Methods: Two different learning methods, i.e. a customized learning kit and PowerPoint teaching slide were used in this pre-post intervention study. The prototype of the customized learning kit was developed based on the psychosocial development of children that emphasized the importance of “children play” in early childhood education. A total of 337 elementary school children around Klang Valley were randomly recruited and grouped into experimental and control group. Results: Both groups showed significant improvement in the disaster-related knowledge level after undergone the knowledge transfer intervention by using different learning methods. Conclusion: With the same learning module utilized in this study, the output highlighted that an effective knowledge transfer intervention could be achieved via a two-way interactive teaching-learning process. Even though the learning materials showed little influence while implementing an effective knowledge transfer, the efficiency of knowledge acquisition that triggers learning interest among learners are crucial factors in marking the sustainable learning at an early age.